A 3D Carpet Cloak with Non‐Euclidean Metasurfaces. Issue 19 (7th July 2020) - Jiang, Zijie; Liang, Qingxuan; Li, Zhaohui; Chen, Tianning; Li, Dichen; Hao, Yang
Abstract: Metasurfaces have opened up a new era of manipulating electromagnetic waves including the implementation of invisibility cloaks, based on their simple design and ultrathin thickness. However, a perfect design of metasurface structures, such as the carpet cloak on non‐Euclidean geometries independent of the state of polarization and the azimuthal angle of wave incidence, remains unrealized in practice. Herein, a new design and fabrication approach which annihilates current defects of metasurface structures is proposed and illustrated by using a rapid prototyping of a 3D spherical carpet cloak. Benefited from its perfectly symmetric distribution of meta‐atoms, the carpet cloak is demonstrated to be fully insensitive to all polarizations and azimuthal angles of incident waves from both simulated and experimental results. The proposed cloak is also electrically large with 7λ0 in length and 1.2λ0 in height, which opens up the possibility of practical applications in areas governed by wave physics. Abstract : A 3D non‐Euclidean metasurface carpet cloak with a spherical geometry in the microwave domain is realized for the first time via a novel design and fabrication method. The perfect rotational symmetry of the meta‐atom distribution enables the carpet cloak to eliminate the performance fluctuations caused by the changes of the polarizations and azimuthal angles, leading to a more practical structure.